Evaluasi Struktur Gedung X di Jakarta Berdasarkan SNI 03-1726-2012 Ketahanan Gempa untuk Struktur Gedung - Sayed Ahmad Fauzan; , Erizal; Asep Sapei (Departemen Teknik Sipil dan Lingkungan, IPB University, 2018)
Earthquake risk in Jakarta is one of intermediate category in Indonesia based on the 2010 seismic hazard map published by the Ministry of Public Works of Republic Indonesia. The purpose of this research was to know the ultimate performance limit of the existing X building in Jakarta. Evaluation of these building was based on guidelines SNI 03-1726-2012, SNI 03-2847-2013 and PPPURG 1987. The structure model of X building was designed and analyzed using ETABS Version 9.7.2. The result showed value of story drift was affected by dynamic response spectrum load, the maximum drift in x–direction is 68.60 mm and y–direction is 101.2 mm. The X building was declared unsafe in performance condition of the ultimate limits. It was important to know the condition of the building that would be affected by earthquake load and to prevent collapse of the building structures that could cause loss of live people in the building and the collisions between buildings. Keywords : building, earthquake, respon spectrum analysis, story drift.